PHENOMICS – POSTGENOMIC SCIENCE IN AGROECOLOGY - Kipen, Viachaslau; Patrin, Maksim; Sitnikov, Maksim (Journal of the Belarusian State University. Ecology, 2026)
High-throughput digital phenotyping (phenomics) is a revolutionary approach in modern plant physiology, located at the intersection of physiology, genetics, information technology, and agroecology. This methodology enables a comprehensive analysis of the phenotypic characteristics of plants with unprecedented accuracy and objectivity, making it an indispensable tool in modern biological research. The integration of phenomics with advanced technological solutions, including multispectral analysis, hyperspectral imaging, and artificial intelligence, opens new perspectives for studying the mechanisms of plant development and their interactions with the environment. The application of phenomic approaches is particularly important in addressing pressing agroecological challenges aimed at increasing crop productivity and developing stress-resistant plant varieties. Modern phenomic research contributes to the optimization of biological resource use and the development of innovative breeding methods, which is of paramount importance for ensuring food security and sustainable development of the agricultural sector. The introduction of digital phenotyping technologies significantly accelerates the development of new plant varieties with improved characteristics, including increased yield, resistance to adverse environmental factors, and optimal resource utilization. Thus, phenomics serves as a fundamental basis for the development of modern agrobiotechnology, integrating the achievements of various scientific disciplines and providing a comprehensive approach to addressing key plant production challenges in the face of global environmental challenges.